Quality of life and self-care awareness, family and colleague care of professional nurses during the COVID-19 Pandemic - Saengsiri, Aem-orn; Chaleoykitti, Saisamorn; Wongsaita, Naiyana; Chatchavalitsakul, Wilairat; Upasen, Ratchaneekorn; Srisupha-olarn, Itsari; Preechawong, Sunida (Thai Journal of Nursing, 2023)
The purposes of this descriptive research were to study quality of life and to study self-care awareness, family and colleagues care in preventing the spread of the COVID-19 of professional nurses during the COVID -19 pandemic. A sample of 1,339 professional nurses who were working in health system, was selected by volunteer sampling. The research tools included 1) general information questionnaire, 2) Professional Quality of Life Scale: Compassion Satisfaction and Fatigue version 5 (ProQOL) and 3) the questionnaire on self-care awareness, family and colleague care. Data were analyzed using descriptive statistics. Research results revealed that the majority of professional nurses (71.82 %) had quality of life in the subpart of compassion satisfaction at a moderate level. Regarding to compassion fatigue subpart of quality of life, 85.50% and 61.14% of them reported a moderate level of burnout and a low level of secondary traumatic stress dimension respectively. In regard to self-care awareness, the majority of professional nurses reported wearing face masks every time before going outside (95.7%) while only 49.1 percent of them reported regularly using separate dishes, glasses, cups, and eating utensils.